A stochastic integral of operator-valued functions - Tesko, V. A. (Methods of Functional Analysis and Topology, 2008)
In this note we define and study a Hilbert space-valued stochastic integral of operator-valued functions with respect to Hilbert space-valued measures. We show that this integral generalizes the classical Ito stochastic integral of adapted processes with respect to normal martingales and the Ito integral in a Fock space.